Molecular and biochemical characterisation of human casein kinase I alpha splice variants - Yong, Thomas Joon Kin. (2009)
Casein kinase I (CKI), one of the first protein kinases identified biochemically, is a serine/ threonine protein kinase known to exist in multiple isoforms in mammals. It has been shown in mammalian tissues that CKI alpha exists in two or three alternatively spliced variants (Rowles et al., 1991; Zhang et al., 1996; Kuret et al., 1997). Recently, four alternatively spliced variants of CKI alpha (CKIa, CKIas, CKIaLS, CKIa|_)were identified in diverse chicken cell types (Green and Bennett, 1998). To date, only a human CKIas cDNA has been published (Tapia et al., 1994; Fish et al., 1995). Here, I report on the isolation of near full length cDNAs coding for human CKIas and human CKIaL derived from the 4.2 kb mRNA transcripts. Both splice variants are also likely to be encoded by the 2.4 kb mRNA transcripts, generated by employing an alternate polyadenylation signal identified in the longer transcripts. The 4.2 kb mRNA species of both splice variants contain five additional RNA-destabilising AU-rich element (ARE)motifs in their 3' untranslated regions, the 2.4 kb transcripts contain a single ARE; suggesting the longer transcripts may be more rapidly turned over. Compared to human CKIas, human CKIaL contains an additional 28 amino acids after Lys-|52, and a deletion of 12 amino acids after GIV323. In addition, a cDNA coding a potential novel splice variant of human CKIaL, which I have named human CKIaT, has been identified. Human CKkxT lacks the catalytic subdomains I to Vlb (as defined by Hanks et al., 1988)but contains a nine novel amino acids at the amino terminal, followed by the 28 amino acids identified as the insertion and the subdomains VII to XI of the catalytic domain. The regulatory domain of human CKIaT is identical to that of human CKIas but contains an additional eight amino acids at the carboxyl terminal not previously reported in any other CKI alpha. Evidence from attempts at isolating additional independent CKIaT cDNAs, comparison of CKIaT to the human regulator of mitotic spindle assembly-1 (RMSA-1),